Single‐cell deconstruction of post‐sepsis skeletal muscle and adipose tissue microenvironments. Issue 5 (8th July 2020) - Cho, Dong Seong; Schmitt, Rebecca E.; Dasgupta, Aneesha; Ducharme, Alexandra M.; Doles, Jason D.
Abstract: Background: Persistent loss of skeletal muscle mass and function as well as altered fat metabolism are frequently observed in severe sepsis survivors. Studies examining sepsis‐associated tissue dysfunction from the perspective of the tissue microenvironment are scarce. In this study, we comprehensively assessed transcriptional changes in muscle and fat at single‐cell resolution following experimental sepsis induction. Methods: Skeletal muscle and visceral white adipose tissue from control mice or mice 1 day or 1 month following faecal slurry‐induced sepsis were used. Single cells were mechanically and enzymatically prepared from whole tissue, and viable cells were further isolated by fluorescence activated cell sorting. Droplet‐based single‐cell RNA‐sequencing (scRNA‐seq; 10× Genomics) was used to generate single‐cell gene expression profiles of thousands of muscle and fat‐resident cells. Bioinformatics analyses were performed to identify and compare individual cell populations in both tissues. Results: In skeletal muscle, scRNA‐seq analysis classified 1438 single cells into myocytes, endothelial cells, fibroblasts, mesenchymal stem cells, macrophages, neutrophils, T‐cells, B‐cells, and dendritic cells. In adipose tissue, scRNA‐seq analysis classified 2281 single cells into adipose stem cells, preadipocytes, endothelial cells, fibroblasts, macrophages, dendritic cells, B‐cells, T‐cells, NK cells, and gamma delta T‐cells. One day post‐sepsis, the proportion of most non‐immune cell populations was decreased, while immune cell populations, particularly neutrophils and macrophages, were highly enriched. Proportional changes of endothelial cells, neutrophils, and macrophages were validated using faecal slurry and cecal ligation and puncture models. At 1 month post‐sepsis, we observed persistent enrichment/depletion of cell populations and further uncovered a cell‐type and tissue‐specific ability to return to a baseline transcriptomic state. Differential gene expression analyses revealed key genes and pathways altered in post‐sepsis muscle and fat and highlighted the engagement of infection/inflammation and tissue damage signalling. Finally, regulator analysis identified gonadotropin‐releasing hormone and Bay 11‐7082 as targets/compounds that we show can reduce sepsis‐associated loss of lean or fat mass. Conclusions: These data demonstrate persistent post‐sepsis muscle and adipose tissue disruption at the single‐cell level and highlight opportunities to combat long‐term post‐sepsis tissue wasting using bioinformatics‐guided therapeutic interventions.